Scratching the surface of spectacle: Black hypermasculinity and the Television Talent Show - Robinson, Laura Helen Carol (The International Journal of Screendance, 2018)
This study explores the construction of black hypermasculinity in television talent show competitions through the re-valuing of spectacle as an aesthetic experience. Drawing on a screendance analysis of eighteen duet, trio and group performances featured in ITV’s Britain’s Got Talent (BGT) and Sky1’s Got To Dance (GTD) between 2008-2013, this study explores the circulation of black hypermasculinity and the potentiality for an alternate reading of spectacular displays of athleticism. Building upon Kristen Whissel’s concept of the emblematic nature of the special effect in cinema, the re-valuing of televised spectacles reveals themes regarding the black male experience in these competitions. Rather than dismissing these performances as commercial spectacles that recirculate notions of black hypermasculinity, these corporeal and televisual special effects instead highlight the thematic narrative of the reality television journey through themes of aspiration and transformation. Crews constructs images of superheroes, cartoons, animals and cyborgs, manipulated by camera angles and editing, that operate as both light entertainment and a reflection of the young black male experience in mediascope of reality television. The creation of spectacular and glossy images on screen therefore reveals the potentiality of a fluid gender and racialized representation.